Peningkatan Self Efficacy dalam Mengelola Kesulitan Bernafas Melalui Edukasi Manajemen Dispnea pada Pasien PPOK - Ramadhani, Rizkika (Universitas Aisyah Pringsewu, 2018)
COPD is a chronic and progressive disease that requires self-management efforts in the management of the disease. Self-efficacy is an important concept of self-management disease to achieve behavioral change. The research objective was to identify the influence of dyspnea management education toward self-efficacy in managing breathing difficulties in COPD patients. The research design was quasi-experimental by using pretest-posttest with the control group. The number of samples was 34, consist of 17 people in intervention group and 17 people in control group. The results showed that a significant increase toward self-efficacy after given dyspnea management education (p = 0.036). Based on this research, dyspnea management education can be used as an optimal nursing intervention to improve self-efficacy in managing breathing difficulties in COPD patients.